Aboriginal Maple Syrup Values Summary - Chrétien, Annette; Murphy, Brenda; Restoule, Charles; Smits, Melanie (Scholars Commons @ Laurier, 2014)
This report examines the values associated with maple syrup practices in Aboriginal contexts. It is based on fifteen interviews conducted with Aboriginal people who have knowledge of maple syrup practices in Ontario. The interviewees included both First Nations and Metis people.